2020
DOI: 10.1136/bmjspcare-2020-002251
|View full text |Cite
|
Sign up to set email alerts
|

Delirium screening practice in specialist palliative care units: a survey

Abstract: ObjectivesDelirium is common and distressing in palliative care settings. This survey aims to describe current practice regarding delirium identification in specialist palliative care units (SPCU), such as inpatient hospices, in the UK.MethodsAn 18-item anonymous online survey was distributed by Hospice UK to their network of clinical leads (n=223), and to their research mailing list (n=228). The survey was also sent to the chair of the Hospice UK executive clinical leads forum for direct dissemination to foru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…10,22 Currently, the use of delirium screening tools in palliative care is varied and their utility is unclear. 1,23 A recent survey of UK and Irish palliative care physicians reported that 59% do not use a formal screening tool on patients admitted to inpatient palliative care units. 24 There is also variability in the timing of delirium screening and the training of staff performing screening which may limit delirium detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,22 Currently, the use of delirium screening tools in palliative care is varied and their utility is unclear. 1,23 A recent survey of UK and Irish palliative care physicians reported that 59% do not use a formal screening tool on patients admitted to inpatient palliative care units. 24 There is also variability in the timing of delirium screening and the training of staff performing screening which may limit delirium detection.…”
Section: Introductionmentioning
confidence: 99%
“…24 There is also variability in the timing of delirium screening and the training of staff performing screening which may limit delirium detection. 23 Furthermore, many delirium screening tools were not specifically developed for use in palliative care populations, who are often highly symptomatic, easily fatigued, and more likely to require non-verbal or observational assessments. 25,26 As a result, studies which validate delirium screening tools in other care settings may not be generalizable to palliative care settings.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of UK palliative care specialists reported the majority (68%) only screened for delirium when suspected clinically, and few (5%) screened routinely on admission to palliative care units 43 . Only a third of respondents (37%) used assessment tools to screen for delirium, despite international guidance advocating their use.…”
Section: Discussion/implicationsmentioning
confidence: 99%
“…The 4AT is recommended for identifying patients with delirium 14 , and is currently used in palliative care settings [41][42][43] , but has not been validated for delirium screening in a terminally ill population.…”
Section: ' A's Test (4at) 22mentioning
confidence: 99%
“…16 Recent systematic reviews have found a lack of high quality evidence to support routine use of medication, including antipsychotics, for delirium. 17,18 However, surveys of palliative care clinicians have identified that current practice is poorly aligned with current evidence and guidelines; there is a lack of routine screening for delirium 19,20 and antipsychotics and benzodiazepines for delirium are more commonly used than by clinicians working in other specialties. 21…”
Section: Introductionmentioning
confidence: 99%